Putusan MK Nomor 86/PUU-X/2012 Dilihat dari Perspektif Fiqih Siyasah: Respon Politik Hukum Masyarakat Sipil melalui Judicial Review UU No. 23 Tahun 2011 Tentang Pengelolaan Zakat - Imron Hamzah (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2022)
After the issuance of the Zakat Management Act No. 23 of 2011 as a part of which was intended to improve the previous Law (Law No. 38 of 1999) it still reaped contra from the community, especially private amil zakat institutions. Considering that the existing laws were deemed insufficient to accommodate the potential development of zakat in Indonesia, Commission VIII of the House of Representatives of the Republic of Indonesia formulated the new law on zakat management. However, since Law no. 38 of 1999, which previously had regulated the Management of Zakat, followed by a new law instead caused controversy among practitioners, academics, the public, the Amil Zakat Institution (LAZ) and other stakeholders. The fact that proves the existence of this controversy is the application for a judicial review to the Constitutional Court/MK. The applicants submitted a judicial review of several articles in the zakat management law based on four main points, namely the existence of criminalization, centralization, subordination, and marginalization. This effort is a legal political response and a manifestation of the role of the socio-political power of civil society in Indonesia, therefore this paper describes what and how the legal political efforts of civil society represented by several LAZ (Amil Zakat Institutions) respond through a legal effort called judicial review of Law No. 23 of 2011 concerning Zakat Management and proven successful with the issuance of the Constitutional Court Decision Number 86/ PUU-X/2012.